Odontoglifia en una población prehispánica de tradición cultural sonso ubicada en Yumbo, Valle del Cauca, Colombia - Rodríguez-F., Carlos David (Revista Facultad de Odontología Universidad de Antioquia, 2009)
This article describes the intertubercular morphology (Odontogliphycs) in permanent dentition of the population buried in the Guacandá pre-Hispanic cemetery located in Yumbo, Valle del Cauca (Colombia), and evaluates the temporal variability of these traits between VI and XVI centuries A.D. 27 individuals between 5 and 25 years of age with partial complete dentitions were analyzed; 30 grooves, 6 of them in upper premolars, 6 in lower premolars, 8 in upper molars, and 10 in lower molars were identified. A considerable intertubercular morphology variation was found in this pre-Hispanic population. The dental morphogenetic diversification suffered by the primitive inhabitants of Guacandá is evident, and it is believed to be caused by the contact processes between the Guacandá population and other populations in the region as well as to the gene flow.